Incômodo decorrente do ruído na escola em professores com e sem distúrbios vocais - Matos, Elaine Cristina Gemaque de (2008)
There are several aspects that permeate the area of health of the worker, but there is no doubt that working conditions, including environmental risks and organizational. The voice disorders may be related to inadequate competition noise in classes, resulting from the high levels of sound pressure. Polls that can recognize and measure the noise in schools, related to disturbances vocal, and its possible effects on health represent important grant for the planning of the shares of Speech Therapist. The purpose of this study was to evaluate the noise nuisance arising from the school, teachers with and without disturbances voice of two schools in the city of Sorocaba network and examine the possible association between the complaints of teachers and disturbances voice evaluated in the examination of nasovideolaringoscopy. This research was an epidemiological study of the type of investigation where cross were selected 2 schools in different locations in the city of Sorocaba-SP and categorized in E1 (27 teachers) and E2 (26 teachers). Nasovideolaringoscopy of examinations were performed in 53 of the framework active teachers of the schools and after the examinations teachers responded 2 questionnaires regarding complaints of health and nuisance of noise. The results showed that teachers have more of E2 disturbances voice than the teachers of E1; Teachers of E1 have more complaints of general health and itch in the ear, for the E2 is the most frequent symptom of infection hearing, the complaint of allergy was the most reported in both schools; symptoms of stress and headache was the most frequent in teachers with a voice disorder, while the symptoms of heartburn and sick obtained co-statistical with teachers with a voice disorder, the Internal noise was the main source of discomfort reported by teachers with a voice disorder of E1, the E2 has been the external noise; teachers from E1 showed greater recognition of the effects of noise on health; statistical tests have shown that the symptoms of Stress / irritation are co-related disorders teachers without a voice